2018
DOI: 10.1111/1750-3841.14110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enterococcus faecium NRRL B‐2354 as a Surrogate for Salmonella During Extrusion of Low‐Moisture Food

Abstract: Food Safety Modernization Act requires the food industry to validate processing interventions. This study validated extrusion processing and demonstrated that E. faecium NRRL B-2354 is an acceptable surrogate for extrusion of low-moisture products. The developed response surface model allows the industry to identify process conditions to achieve a desired lethality for their products based on composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The fat content did not have a significant effect on the D-values of the RSM and therefore was not included in the final model. Although the protective effect of fat on Salmonella inactivation has been observed in many high-moisture foods (Ahmed et al, 1995;Verma et al, 2018), a similar protective effect was not found in milk powders. A protective effect of fat was not observed in milk powder during this short storage time (5 d).…”
Section: Thermal Resistance Of Salmonella In Wmp and Nfdmmentioning
confidence: 76%
See 2 more Smart Citations
“…The fat content did not have a significant effect on the D-values of the RSM and therefore was not included in the final model. Although the protective effect of fat on Salmonella inactivation has been observed in many high-moisture foods (Ahmed et al, 1995;Verma et al, 2018), a similar protective effect was not found in milk powders. A protective effect of fat was not observed in milk powder during this short storage time (5 d).…”
Section: Thermal Resistance Of Salmonella In Wmp and Nfdmmentioning
confidence: 76%
“…Hildebrandt et al (2016) suggested that a lawn-based pelletized inoculum, which was used in this study, could provide a stable Salmonella population before isothermal treatment and yield consistent D-values. Several studies have shown that this lawn-based inoculation method provides consistent and stable Salmonella inoculated samples of different low-a w foods, such as spices (Chen et al, 2019;, oat and wheat flour (Liu et al, 2018;Verma et al, 2018), and egg white powder (Wei et al, 2020). Also, this wet inoculation method could simulate a common contamination scenario of milk powders, in which Salmonella-contaminated liquid drips from the roof of a processing plant into the powders being processed.…”
Section: Stability Tests Of Powder Inoculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that all the parameters except temperature had a significant effect on the mean residence time during the single‐screw extrusion of oat flour. Additionally, Verma and Subbiah (2020) reported that replacing the screw speed with mean residence time did not significantly improve their previously developed inactivation models for Salmonella and E. faecium (Verma et al., 2018a, 2018b). Therefore, it was suggested to use screw speed instead of mean residence time for conducting the extrusion validation studies as it is easier and convenient for the food processors to control.…”
Section: Process Technologies For Microbial Inactivation In Low‐moist...mentioning
confidence: 99%
“…Also, due to the difficulty of directly introducing the target pathogen into the processing plant, the use of a surrogate to replace the pathogen is recommended by FDA (2013) to conduct the validation study in the industrial processing plant. Several studies (Bianchini et al, 2014;Liu et al, 2018;Verma et al, 2018;Wei et al, 2018) have previously demonstrated that Enterococcus faecium NRRL B-2354 is a suitable surrogate for Salmonella during thermal processing of low water activity foods.…”
Section: Introductionmentioning
confidence: 99%